2022
DOI: 10.1039/d2tb00644h
|View full text |Cite
|
Sign up to set email alerts
|

An injectable thermosensitive hydrogel with a self-assembled peptide coupled with an antimicrobial peptide for enhanced wound healing

Abstract: Wound dressing based on thermosensitive hydrogel shows advantages over performed traditional dressings such as rapid reversible sol-gel-sol transition property and the capacity of filling the irregular wound area. Herein, RA-Amps...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…Excellent skin healing promoting effect was observed in a mouse skin infection model (Figure 8D). [103] Wang et al prepared injectable hydrogels consisting of polylysine (𝜖-PL) and carboxymethyl chitosan (CMCS) for medical applications. [104] Similarly, Zhu et al designed a hydrogel consisting of carboxymethyl chitosan (CMC) and a peptide dendrimer AMP (G3KP).…”
Section: Self-assembled Peptide-based Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Excellent skin healing promoting effect was observed in a mouse skin infection model (Figure 8D). [103] Wang et al prepared injectable hydrogels consisting of polylysine (𝜖-PL) and carboxymethyl chitosan (CMCS) for medical applications. [104] Similarly, Zhu et al designed a hydrogel consisting of carboxymethyl chitosan (CMC) and a peptide dendrimer AMP (G3KP).…”
Section: Self-assembled Peptide-based Hydrogelsmentioning
confidence: 99%
“…Reproduced with permission. [ 103 ] Copyright 2022, Royal Society of Chemistry. E) (a) Schematic Illustration of OCMC/G3KP hydrogel bioadhesives.…”
Section: Skin Wound Bacterial Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, gelatin is liquid at 37 °C and gels below 30 °C [ 73 ], whereas poly(N-isopropyl acrylamide) (PNIPAM) is liquid at room temperature and gels at physiologic temperatures [ 74 ]. With the aim of designing self-forming antimicrobial hydrogels that enhance wound-healing, Feng and coworkers reported the development of PNIPAM hydrogels containing a joint peptide consisting of an AMP RRWRVIVKW and RADA16 (Ac-RADARADARADARADA-NH 2 ), termed RA-Amps [ 75 ]. The AMP used in this study was found to disrupt bacterial cell membranes and inhibit growth [ 76 , 77 ].…”
Section: Self-assembling Amp Hydrogelsmentioning
confidence: 99%
“…The results suggest that F127/CA/Gx hydrogel can envelop cells for tissue engineering ( Yap and Yang, 2020 ). Prosthodontic-inspired photopolymerization stimulated by blue light is a gentle process for initiating the polymerization of monomers ( Chen et al, 2020 ; Downs et al, 2020 ; Feng et al, 2022 ), The blue light initiator in the hydrogel system commences hydrogel cross-linking. Human Bone contains 50%–70% inorganic calcium and phosphorus.…”
Section: Promoting Bone Regeneration By Hydrogelsmentioning
confidence: 99%